Molecular identification of two Culex (Culex) species of the neotropical region (Diptera: Culicidae) - Laurito, Magdalena (2017)
Culex bidens and C. interfor, implicated in arbovirus transmission in Argentina, are sister species, only distinguishable by feature of the male genitalia; however, intermediate specimens of the species in sympatry have been found. Fourth-instar larvae and females of both species share apomorphic features, and this lack of clear distinction creates problems for specific identification. Geometric morphometric traits of these life stages also do not distinguish the species. The aim of the present study was to assess the taxonomic status of C. bidens and C. interfor using two mitochondrial genes and to determine the degree of their reproductive isolation using microsatellite loci. Sequences of the ND4 and COI genes were concatenated in a matrix of 993 nucleotides and used for phylogenetic and distance analyses. Bayesian and maximum parsimony inferences showed a well resolved and supported topology, enclosing sequences of individuals of C. bidens (0.83 BPP, 73 BSV) and C. interfor (0.98 BPP, 97 BSV) in a strong sister relationship. The mean K2P distance within C. bidens and C. interfor was 0.3% and 0.2%, respectively, and the interspecific variation was 2.3%. Bayesian clustering also showed two distinct mitochondrial lineages. All sequenced mosquitoes were successfully identified in accordance with the best close match algorithm. The low genetic distance values obtained indicate that the species diverged quite recently. Most morphologically intermediate specimens of C. bidens from CoÂrdoba were heterozygous for the microsatellite locus GT51; the significant heterozygote excess observed suggests incomplete reproductive isolation. However, C. bidens and C. interfor should be considered good species: The ventral arm of the phallosome of the male genitalia and the ND4 and COI sequences are diagnostic characters.